2013
DOI: 10.5603/fhc.2013.0012
|View full text |Cite
|
Sign up to set email alerts
|

CCN1 expression in interleukin-6 deficient mouse kidney in experimental model of heart failure

Abstract: Chronic heart failure often leads to worsening of the renal function. Mediators of this process include inflammatory and neuroendocrine factors. CCN1 (Cyr 61), a member of growth factor-inducible immediate early genes, which modulates inflammation and fibrogenesis, is excreted with urine in the early phase of acute renal injury and may be involved in the pathogenesis of the cardiorenal syndrome. The aim of the study was to evaluate CCN1 protein abundance and localization in the kidney of IL-6-deficient C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…One, randomly taken left or right hippocampus was used for Western blot, while the other for quantitative Real-Time PCR. Genotype of mice was confirmed by polymerase chain reaction as described previously (Bonda et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…One, randomly taken left or right hippocampus was used for Western blot, while the other for quantitative Real-Time PCR. Genotype of mice was confirmed by polymerase chain reaction as described previously (Bonda et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the elevated CCN1 levels were significantly associated with the severity of acute heart failure in a cohort of 183 patients [8]. In addition, animal heart failure experiments also revealed that the expression of CCN1 protein was increased [9][10][11].…”
Section: Introductionmentioning
confidence: 92%
“…There is mounting evidence that CCN1 plays critical roles in cardiovascular development, embryogenesis, wound healing, inflammation regulation, and fibrogenesis (Bonda et al, 2012(Bonda et al, , 2013(Bonda et al, , 2015Lau, 2011).…”
Section: Ccn1 In Heart Fibrosismentioning
confidence: 99%
“…Immunohistochemical analysis in most cardiac tissue specimens, obtained from victims died of sudden cardiac death, revealed that CCN1 may be associated with myocardial ischemic morphology and cardiac hypertrophy, and ischemia is the possible reason for the increased expression of myocardial CCN1 protein (Hilfiker-Kleiner et al, 2004;Papetta et al, 2013). Also, in several animal experiments, it was found that CCN1 expression increased in cardiac tissue with fibrosis and cardiac-specific expression of CCN1 resulted in the reduction of cardiac fibrosis in murine models of cardiac diseases (Bonda et al, 2012(Bonda et al, , 2013(Bonda et al, , 2015Meyer et al, 2016). Furthermore, one in vitro experiment confirmed that CCN1 increased the survival of myocytes by activating the integrin β1-Akt pathway under conditions of oxidative stress, whereas knockdown of CCN1 decreased the number of surviving cells under these conditions (Yoshida et al, 2007).…”
Section: Ccn1 In Heart Fibrosismentioning
confidence: 99%
See 1 more Smart Citation